2023
DOI: 10.1108/ijppm-07-2022-0328
|View full text |Cite
|
Sign up to set email alerts
|

Working capital and firm performance: role of COVID-19 disruption

Abstract: PurposeThis study examines the performance effect of working capital for a large sample of Indian manufacturing firms in light of supply chain disruption, i.e. the COVID-19 pandemic.Design/methodology/approachThis study is based on secondary data collected from the Prowess database on Indian manufacturing firms listed on the Bombay Stock Exchange (BSE) 500. Panel data regression analyses are used to estimate all models. Moreover, this study has employed robust standard errors to consider for heteroscedasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Overall, the research literature indicates that the COVID-19 pandemic has led to significant changes in working capital management strategies for manufacturing firms, with many facing challenges related to cash flow, operational costs, and profitability Tarkom 2022;Hamshari et al 2022;Wadesango et al 2022;Pant et al 2023). In this study, our findings confirm that the COVID-19 crisis caused Iranian manufacturing companies to adopt working capital investment policies and also seek to increase the current ratio (CR) and cash to current assets (CTCA) ratio, while avoiding the policies of WC financing, operating cycle (OC), and receivables turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the research literature indicates that the COVID-19 pandemic has led to significant changes in working capital management strategies for manufacturing firms, with many facing challenges related to cash flow, operational costs, and profitability Tarkom 2022;Hamshari et al 2022;Wadesango et al 2022;Pant et al 2023). In this study, our findings confirm that the COVID-19 crisis caused Iranian manufacturing companies to adopt working capital investment policies and also seek to increase the current ratio (CR) and cash to current assets (CTCA) ratio, while avoiding the policies of WC financing, operating cycle (OC), and receivables turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this negative effect was mitigated by companies receiving government incentives (deferred taxes and investment tax credits). Through an analysis of Indian manufacturing firms, Pant et al (2023) found that these firms suffered financially post-COVID-19, since they significantly lacked the working capital to run day-to-day operations. In another study conducted in the Indian context, Kumar and Olasiuk (2024) showed a negative relationship between the cash conversion cycle (CCC) and leverage ratio with ROA during the challenging environment of the COVID-19 pandemic and confirmed that corporate profitability improves when firms reduce leverage, favor equity-based financing, and seek to increase the current ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This may lead to a higher cost of WC and weigh down WCF. Empirical investigations show that Indian manufacturing firms, predominantly driven by imported inputs, have experienced high financial distress, with higher friction, costly trade credit, and a crunch in WC (Devalkar and Krishnan 2019;Pant et al 2023). Hence, it is pertinent to examine how firm foreign currency borrowings drive working capital financing to compensate for credit crunch amidst financial distress.…”
Section: Introductionmentioning
confidence: 99%